Characteristics of the population and habitat of Chairophon plicatus in Lowo Cave, Gresik Regency - Pratama, Muhammad Iqbal; Aulia, Tia (Genbinesia Journal of Biology, 2022)
Bats are one of the animals that have great environmental services. Habitat destruction is one of the reasons for the reduction in the number of bats. the study of the habitat and population of bats is important considering the damaged habitat. This research was conducted by using the caving technique and sex comparison analysis. These cave-dwelling bats occupy a humid location, lack of light and temperatures ranging from 34°C. cave-dwelling bats are dominated by females.